2021
DOI: 10.1021/acs.jnatprod.1c00758
|View full text |Cite
|
Sign up to set email alerts
|

Amakusamine from a Psammocinia sp. Sponge: Isolation, Synthesis, and SAR Study on the Inhibition of RANKL-Induced Formation of Multinuclear Osteoclasts

Abstract: A simple methylenedioxy dibromoindole alkaloid, amakusamine (1), was isolated from a marine sponge of the genus Psammocinia, and its structure was determined from spectroscopic data, time-dependent density-functional theory calculations, and synthesis. Compound 1 inhibited the receptor activator of nuclear factor-κB ligand (RANKL)-induced formation of multinuclear osteoclasts with an IC 50 value of 10.5 μM in RAW264 cells. The structure−activity relationship of 1 was also investigated with synthetic derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Compounds 231 and 232 were isolated from the bark of Voacanga africana , and they are the first monoterpene trisindole alkaloids containing a vobasine–aspidosperma–aspidosperma skeleton [ 65 ]. Similarly, compound 233 is the first methylenedioxy dibromoindole alkaloid exhibiting antiosteoporosis activity [ 66 ]. Additionally, compound 234 is a dibrominated β-carboline sulfamate, one of the only 11 indole sulfamate-containing marine natural products reported in the Marin Lit.…”
Section: Isolation Of Novel Indole Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 231 and 232 were isolated from the bark of Voacanga africana , and they are the first monoterpene trisindole alkaloids containing a vobasine–aspidosperma–aspidosperma skeleton [ 65 ]. Similarly, compound 233 is the first methylenedioxy dibromoindole alkaloid exhibiting antiosteoporosis activity [ 66 ]. Additionally, compound 234 is a dibrominated β-carboline sulfamate, one of the only 11 indole sulfamate-containing marine natural products reported in the Marin Lit.…”
Section: Isolation Of Novel Indole Alkaloidsmentioning
confidence: 99%
“…Upon initial failure of a direct debromination of 5,6-methylenedioxyindole, they used an alternative reaction scheme containing three steps and obtained an overall yield of 56% ( Figure 18 ). The synthetic method also enabled the synthesis of 15 synthetic derivatives of compound 233 ( 294 to 308 ) for an SAR analysis ( Figure 19 ) [ 66 ]. The synthesis involved the reaction of 6-nitropiperonal ( 291 ) with NBS in concentrated H 2 SO 4 , producing 292 .…”
Section: Synthesis Of Indole Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Replacement of the bromines with chlorines significantly reduced activity. Evaluation of the potencies of N -acyl derivatives demonstrated that those with C 2 − C 8 -alkyl chains were equipotent or slightly more potent, but those with a C 14 -alkyl chain and benzoyl derivative were inactive even at 50 µM [ 53 ].…”
Section: Marine Natural Products That Inhibit Osteoclastogenesismentioning
confidence: 99%